Options of Intergovernmental Fiscal Relations Reform in the Ukraine - Lunina, Inna (Ekonomika, 2009)
Reform of the system of public finance is a key problem in the transformation processes of the Ukraine’s economy. Development of efficient methods of financial policy is especially important in the context of strategic challenges of economic growth, the competitiveness of the national economy, and convergence of the level of socio-economic development between different regions of the country. Most elements of the modern system of the Ukraine’s public finance were formed as far back as during the Soviet era, under the conditions of command and administrative economy, when neither the state budget, nor the local ones played any active role, but were a mere monetary reflection of the plans of socio-economic development. On the other hand, in market economies, public finance plays an important role in the provision of economic growth and efficient use of national economic resources, as well as in the solution of the problems related to social equity. During recent years, the attempt to reform intergovernmental fiscal relations in the Ukraine have failed either to create a well-balanced system for the distribution of powers between central state authorities and local government, or to elaborate adequate and transparent mechanisms for the formation of local budgets. The reason is that most problems of the local budgets are mostly treated by policy makers and local authorities in the context of the need to provide local budgets with “sufficient” financial resources. We emphasize that creation of an efficient budget system is not limited to a mere re-distribution of revenues between central and local budgets. Investigation of theoretic and methodological foundations of the development of the components of the system of public finance and intergovernmental fiscal relations in the Ukraine let us conclude that such development should be based on the use of economic principles and criteria as to the distribution of powers between the central authorities and local government. Furthermore, a consistent fiscal policy is needed, which would promote not only the convergence between the local budgets’ expenditures, but also, and first of all, the regions’ socio-economic development.